2012
DOI: 10.4244/eijv8i1a17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a drug-eluting stent with a biodegradable polymer in an unselected patient population: the NOBORI 2 study

Abstract: The promising results previously observed in lower risk patients can be replicated in daily practice. As expected, in off-label indications, rates of adverse events were higher. Nevertheless, our results suggest the good and sustained performance of this stent system in high-risk patients with significant comorbidities and/or complex lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 28 publications
4
29
2
Order By: Relevance
“…38 Preclinical and imaging data were also supportive for the biocompatibility of the Nobori BES, because a lower inflammatory response in the stented segments, and rapid recovery of endothelial function with preserved endotheliumdependent vasomotion at adjacent stent segments were demonstrated for the Nobori BES as compared with the SES. 39, 40 The results of this meta-analysis are also in line with the 1-year data from the NOBORI 2 registry, 41 in which a total of 3,067 patients were enrolled. Indeed, TLR and definite/probable ST rates were 2.2% and 0.7% in the NOBORI 2 registry, compared with 3.2% and 0.55%, respectively in the present study.…”
Section: As Reported Insupporting
confidence: 64%
“…38 Preclinical and imaging data were also supportive for the biocompatibility of the Nobori BES, because a lower inflammatory response in the stented segments, and rapid recovery of endothelial function with preserved endotheliumdependent vasomotion at adjacent stent segments were demonstrated for the Nobori BES as compared with the SES. 39, 40 The results of this meta-analysis are also in line with the 1-year data from the NOBORI 2 registry, 41 in which a total of 3,067 patients were enrolled. Indeed, TLR and definite/probable ST rates were 2.2% and 0.7% in the NOBORI 2 registry, compared with 3.2% and 0.55%, respectively in the present study.…”
Section: As Reported Insupporting
confidence: 64%
“…At one-year, the primary endpoint (MACE) occurred in 4 (1.6%) patients. This is significantly lower than the 5.0% that was observed in the Nobori DES system (p = 0.014) and the 4.5% that was noted in BioMatrix stent (p = 0.028) [15] [16]. Moreover, ST was reported in only one patient (0.4%).…”
Section: Discussioncontrasting
confidence: 41%
“…of 12 months is too short to off er a complete description of the safety profi le of the biolimus-eluting stent. In the NOBORI 2 study, 26 which assessed the biolimus-eluting Nobori stent, very low stent thrombosis rates were seen 12-24 months (0·10%) 26 and 24-36 months (0·10%) after implantation. 27 By contrast, results of the LEADERS trial showed that the sirolimus-eluting Cypher stent has a yearly incidence of very late stent thrombosis of about 0·6%.…”
Section: Discussionmentioning
confidence: 99%